A Simple Microcontroller-Based 4-20 mA Current Loop Receiver for Sensors with Current Transmitters - Arif Surachman; A. Suhendi; Maman Budiman; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (Jurnal Otomasi Kontrol dan Instrumentasi, 2010)
A current loop receiver system based on a microcontroller has been developed. The current loop receiver system can serve 8 gas sensors with 4-20 mA outputs, which are handled by employing a multiplexer. The data acquisition of the system is composed of a common operational amplifier-based current loop receiver, a CD4051 multiplexer, an ADS7822 serial analog to digital converter (ADC), and an AT89S52 microcontroller. The measured gas concentration is displayed on the 7-segments or transmitted to a personal computer via the RS232 serial communication to be processed by the Microsoft Excel. Additional functions such as gas concentration level warning and error code display are also provided. Keywords:4-20 mA, Current loop, Microcontroller, Receiver, Transmitter